MANAJEMEN PEMERINTAHAN KABUPATEN KUANTAN SINGINGI DALAM PENCEGAHAN KEBAKARAN LAHAN DAN HUTAN TAHUN 2013-2015 - Nindya Septi Destari; Auradian Marta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Prevention of fire forest and farm in Sub-Province Kuantan Singingi not yet is optimal, this matter can be seen from still lower him mount awareness of society and habit of society clearing land by burning. Inwrought organization chart team of operation of fire farm and Sub-Province Kuantan Singingi not yet shown result of optimal this matter can be proved there is still be found fire dot (spot hot) in Sub-Province Kuantan Singingi although still pertained to lower in Province of Riau. Result of research show planning in prevention of fire of forest and farm in Sub-Province Kuantan Singingi need the existence of attention of government to provide budget fund, need the existence of the division of region to facilitate reach if happened fire and need elementary plan in knowing condition especially at dry season and of rutinitas monitoring. Co-Ordinate in prevention of fire of forest and farm in Sub-Province Kuantan Singingi not yet walked at ease goodness co-ordinate into and also exit coordination. Execution in prevention of fire of forest and farm in Sub-Province Kuantan Singingi good enough although still there are a lot of constraint. Evaluate in prevention of fire of forest and farm in Sub-Province Kuantan Singingi have walked but not yet maximal because there are insuffiency especially the problem of medium and financing of basic facilities supporter. Resistor factor not yet is optimal of Inwrought Team him in prevention of fire of forest and farm in Sub-Province Kuantan Singingi its minim is availibility of fund, and facilities of basic facilities supporter which still less, less professional and also the straightening of environmental law which still very low so that if happened fire of forest and farm hence Team of overcoming cannot work maximally.